Influence of Urena lobata Fibre Treatment on Mechanical Performance Development in Hybrid Urena lobata: Fibre/Gypsum Plaster Composites - Jerum Biepinwoh Kengoh; Ekane Peter Etape; Beckley Victorine Namondo; Josepha Foba-Tendo; Yakum Renata Nafu; Betene Ebanda Fabien (Advances in Materials Science and Engineering)
Autogenous shrinkage is related to the chemistry and changes in the internal structure of the cement concrete paste on drying. This problem of drying shrinkage in early stages that occur without any moisture transfer to the surrounding environment has triggered the incorporation of fibres in the cement concrete matrix to fill the micropores and control cracking (autogenous shrinkage). This study aimed at investigating the potential use of Urena lobata (UL) fibre as microreinforcement in enhancing mechanical properties of hybrid UL-fibre/gypsum cement composites used for plasters. The fibre was harvested from the coastal region of Cameroon and treated with 0.06 M NaOH over different periods. Dispersion of treated fibre bundles in the composite (at Wt. % UL-fibre dosages of 0, 1.5, 2.5, and 3.5) was facilitated by blending with the cement paste which also helped to improve interfacial bonding between the fibre and the cement matrix. The moisture/water absorption and flexural properties within the hardened cement matrix were quantitatively assessed, and it was observed that the incorporation of treated fibre accelerated the hydration process. The test results showed an increment in compressive strength and reduction in autogenous shrinkage for the hybrid UL fibre/gypsum cement composites, while lower percentage additions (less than 2.5%) of untreated fibre appeared to have adverse effects on specimens. It was observed that properly dispersed (blended) treated UL fibres filled the fine pores in the cement matrix by providing an additional nucleation site that resulted in a denser microstructure, which in turn enhanced the strengths and limited the autogenous shrinkage.